2022
DOI: 10.4168/aair.2022.14.2.273
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Quality of Life and Mental Health in Patients With Atopic Dermatitis, Asthma and Allergic Rhinitis Using a Nation-wide Database, KNHANES VII

Abstract: Purpose This study investigated mental health status and quality of life in allergic disease patients compared with non-allergic controls. Methods This study used nationwide, population-based, cross-sectional data from the Korean National Health and Nutrition Examination Survey from 2016 to 2018. The propensity matching score was used to balance age and sex distributions between the allergic disease groups and corresponding controls. Atopic dermatitis (n = 446) and asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Correlations and hierarchical regressions were conducted on 1140 caregivers of grade one/two schoolchildren and 1048 grade eight/nine schoolchildren. Correlations revealed that lower HRQOL was associated with higher severity of eczema, asthma, and allergic rhinitis, which is consistent with patterns reported in other regions 5,24,25 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Correlations and hierarchical regressions were conducted on 1140 caregivers of grade one/two schoolchildren and 1048 grade eight/nine schoolchildren. Correlations revealed that lower HRQOL was associated with higher severity of eczema, asthma, and allergic rhinitis, which is consistent with patterns reported in other regions 5,24,25 …”
Section: Discussionsupporting
confidence: 89%
“…Correlations revealed that lower HRQOL was associated with higher severity of eczema, asthma, and allergic rhinitis, which is consistent with patterns reported in other regions. 5,24,25 This study is the first to account for the totality impact of three of the most prevalent pediatric allergic diseases with CAS. The findings suggest that CAS is a key indicator of HRQOL for both populations.…”
Section: Pedsql-schoolmentioning
confidence: 99%
“…Likewise, similar results were concluded in a national study based in France, in which the findings revealed that asthma and AR did not impair the quality of life in terms of mental disability and well-being [ 26 ]. Another recently published nationwide database study revealed a significant difference between the asthma/AR group and the control group in the presence of strong psychological stress, psychiatric consultations, and depression with increased risk in asthma patients (odds ratio (OR): 3.03, 95%CI: 1.29-7.09) [ 27 ]. Moreover, a cross-sectional study conducted among the French population to evaluate the quality of life of asthmatic patients affected by AR revealed that the severity of AR significantly increased the severity of asthma [ 17 ] and was associated with worse asthma control and poor quality of life [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…AD is less common in females aged 75–99 years old in comparison with males of that age, but more common in females aged 18–74 years old 3 . AD does not only increase a person's socioeconomic burden, but also it negatively impacts patients' and their family members' quality of life 4–7 . Although AD is generally considered as a skin disease, more and more evidence suggests it can impact other organs.…”
Section: Introductionmentioning
confidence: 99%
“…3 AD does not only increase a person's socioeconomic burden, but also it negatively impacts patients' and their family members' quality of life. [4][5][6][7] Although AD is generally considered as a skin disease, more and more evidence suggests it can impact other organs. Previous studies have shown that AD is a risk factor for both depression and anxiety.…”
mentioning
confidence: 99%